Bilateral pneumothorax following an acupuncture - Khor, CC; Leong, Tan Toh (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Acupuncture is a form of complementary medicine that has been practiced in China for thousands of years. Adverse effect of acupuncture is rarely reported in local literature. This is a case of a patient who developed bilateral pneumothorax following an acupuncture session. A 63-year-old lady with no significant medical illness presented with sudden onset of shortness of breath half an hour following acupuncture and massage session by traditional medicine practitioner. On examination, she was tachypnoiec and there was reduced air entry bilaterally on lung auscultation. Urgent portable chest X-ray was done and it showed bilateral pneumothorax. Bilateral chest tubes were inserted. Patient was discharged well following five days of hospitalization. As acupuncture is gaining popularity among Malaysian population, medical practitioners need to increase their awareness and knowledge regarding the adverse effect of such alternative practice.